Legal Protection Challenges for Village Midwives in Maternal and Neonatal Emergency Referrals: A Qualitative Study. - Damayanti, Fitriani Nur; Umabaihi, Suaina; Istiana, Siti; Kusumawati, Erna; Poddar, Sandeep (Journal of Nursing & Midwifery Sciences, 2026)
Background: In providing midwifery services, midwives are responsible and accountable professionals who work as women's partners to provide support, care, and advice during pregnancy, childbirth, and the postpartum period. Therefore, it is expected that midwives deserve legal protection. Objectives: The purpose of this study is to describe the implementation, legal protection, and inhibiting factors faced by village midwives regarding referrals for maternal and neonatal emergency cases. Methods: This qualitative research, using a case study method and a sociological juridical approach, was conducted in the Sula Islands, Indonesia, in 2024. The research sample was obtained through technical data collection using interviews with respondents consisting of 8 village midwives, 1 Indonesian Midwives Association administrator, and 1 district health office employee. The sample was taken using a non-probability purposive sampling method until data saturation was reached. The analysis method is a descriptive qualitative approach using thematic analysis (coding, development of categories, and theme extraction). Results: Three main themes and sub-themes were identified: (1) Implementation of referrals (compliance with standard operating procedures (SOP), documentation issues, expired registration certificate, and legal risk concerns); (2) legal protection (perception of protection under the Health Law, challenges when acting beyond authority); (3) inhibiting factors (delayed family decision-making, socio-cultural barriers, financial limitations, distance, infrastructure, and weather conditions). Conclusions: Referrals were partially in accordance with SOPs but were hindered by limited facilities. Midwives feel legally protected when practicing according to competence and SOP, but challenges remain in emergencies. Major obstacles include family decision-making, socio-cultural factors, costs, distance, and infrastructure. The use of the results is to recommend policy improvements, training, and provision of adequate facilities for maternal and neonatal emergency referrals.